Skeleton key of mathematics: A simple account of complex algebraic theories - Littlewood, D. E. (London Hutchinson's university library, 1949)
As the title promises, this helpful volume offers easy access to the abstract principles common to science and mathematics. It eschews technical terms and omits troublesome details in favor of straightforward explanations that will allow scientists to read papers in branches of science other than their own, mathematicians to appreciate papers on topics on which they have no specialized knowledge, and other readers to cultivate an improved understanding of subjects employing mathematical principles.
Keywords: Algebra; Mathematics